REVENUE, EQUITY, AND DEVELOPMENT - TAXATION CHALLENGES IN EMERGING ECONOMIES IN BOTH INDONESIA AND AFGHANISTAN - Barai, Rahimulllah; Zahroh, Fatmawati (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The taxation system is a crucial fundamental issue for some nations and yet developing countries in the development of their economic system of the nation and it is progress. Developing nations are facing some taxation system challenges to implement for the effective economic system to have development progress in all sectors of the country, especially for the people. The aim is to understand Both Indonesia and Afghanistan's taxation system challenges and deeply understand the progress, revenue, and equity and prosper the economy through these important aspects. Drawing data from distinct sources from International organizations, and analyzing government publications, and academic literature, the paper discusses the comprehensive taxation system and deep information about the taxation system and its aspects in both countries Afghanistan and Indonesia. Importantly, comparing the circumstances of the taxation system in both nations is the key to knowing better and making an effective policy and strategy to implement to eliminate the challenges and make it better to have an effective impact on the economy. Interestingly, Indonesia is a nation that implemented effective strategies to have better revenue and and notable taxation system that continues to grapple with issues of equity and uneven distribution of the tax burden. Afghanistan faces different challenges in the taxation system and it is establishment due to a lack of security instability and political issues. The comparison between the two nations' economic systems and it is policies regarding taxation system and their implementation and the importance of addressing the challenges in taxation system and it is an effect on the economic system in developing countries and designing the implementing the policy and strategy for the obstacles and challenges that both governments are facing.